2001
DOI: 10.1002/cbm.373
|View full text |Cite
|
Sign up to set email alerts
|

A survey of female patients in high security psychiatric care in Scotland

Abstract: BACKGROUND: The State Hospital, Carstairs, is the sole high security psychiatric facility for Scotland and Northern Ireland. METHOD: This study compares the female (n = 28) and male (n = 213) patients resident there between 1992 and 1993 using data derived from case-note reviews and interviews with patients and staff. RESULTS: Nearly three-quarters of both the male and female populations had a primary diagnosis of schizophrenia, and secondary diagnoses of substance abuse and antisocial personality disorder wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…An analysis of the hospital population reported that 69% had a diagnosis of schizophrenia, 55% a history of chronic physical disorder, 17% suffered from epilepsy and 89% were on neuroleptic medication. 16 …”
Section: Populationmentioning
confidence: 97%
“…An analysis of the hospital population reported that 69% had a diagnosis of schizophrenia, 55% a history of chronic physical disorder, 17% suffered from epilepsy and 89% were on neuroleptic medication. 16 …”
Section: Populationmentioning
confidence: 97%
“…Deliberate self-harm (DSH) is a frequent occurrence within psychiatric hospital settings (DiClemente, Ponton and Hartley, 1991; James and Warner, 2005; Sansone, Songer and Miller, 2005; Thomson, Bogue, Humphreys and Johnstone, 2001). Defining deliberate self-harm is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Deliberate self-harm in mental health inpatient settings DSH is a common phenomenon within mental health inpatient units and secure facilities, predominantly in female inpatients (for example, James and Warner, 2005;Thomson, Bogue, Humphreys and Johnstone, 2001), although it can be as common in male inpatients. For example, White, Leggett and Beech (1999) found a 45.5% prevalence of self-harm in male patients in one secure unit.…”
Section: Introductionmentioning
confidence: 99%